A nodal inverse problem for second order Sturm-Liouville operators with indefinite weights - Pinasco, Juan Pablo (2015)
In this paper we study an inverse problem for weighted second order Sturm-Liouville equations. We show that the zeros of any subsequence of eigenfunctions, or a dense set of nodes, are enough to determine the weight. We impose weaker hypotheses for positive weights, and we generalize the proof to include indefinite weights. Moreover, the parameters in the boundary conditions can be determined numerically by using a shooting method.